Relationship between serum osteopontin level and atrial fibrillation recurrence in patients undergoing cryoballoon catheter ablation - Hacı Murat Güneş; Gamze Babur Güler; Ekrem Güler; Gültekin Günhan Demir; Filiz Kızılırmak Yılmaz; Mehmet Onur Omaygenç; Ayşe İstanbullu Tosun; Taylan Akgün; Bilal Boztosun; Fethi Kılıçarslan (KARE Publishing, 2017)
Objective: Atrial fibrillation (AF) is the most common sustained arrhythmia and is associated with increased morbidity and mortality. Atrial fibrosis augments recurrence rate following AF catheter ablation. Osteopontin is a multifunctional molecule involved in several pathophysiological pathways, including fibrosis. Presently described is investigation of relationship between serum osteopontin level and AF recurrence after AF cryoablation. Methods: The study was designed to be prospective and observational; 60 patients with paroxysmal (n=47) and persistent (n=13) AF were included. Osteopontin level was measured both before and 6 months after AF ablation with cryoballoon. Results: Preprocedure and postprocedure osteopontin level did not differ between the 2 groups of AF patients (p=0.286, p=0.493, respectively). Postprocedure osteopontin level was significantly higher compared with preprocedure value (32.18 ng/mL vs 15.58 ng/mL; p=<0.001). Left atrial diameter, AF type, and preprocedure osteopontin level were related to AF recurrence (p≤0.05). An age-adjusted multivariate logistic regression analysis was conducted to determine independent predictors of AF recurrence. Among these, AF type (β=2.211; p=0.004; odds ratio [OR]: 9.124; 95% confidence interval [CI]: 2.026-41.094) was found to be the most important factor related to AF recurrence. Preprocedure osteopontin level also predicted AF recurrence independently (β=0.059; p=0.048; OR: 1.061; 95% CI 1.001-1.125). Conclusion: Study results revealed persistency of AF and high preprocedure osteopontin level independently predicted AF recurrence in patients undergoing cryoballoon AF ablation. Association of a biochemical marker with AF recurrence might be beneficial to selection of appropriate patients for cryoballoon procedure and assessment of long-term procedural success.